Social Behavior of Youth in The Old City of Semarang Post Revitalization - Aminuddin, Ilham; Suyahmo, Suyahmo; Atmaja, Hamdan Tri (Universitas Negeri Semarang, 2023)
The Old City of Semarang revitalization has succeeded in becoming a tourist attraction. The development of the old town is only in the field of tourism. The attractiveness of the old city as a cultural heritage with social, cultural, and historical values has yet to be seen. The purpose of this article is to analyze the meaning of adolescents towards the Old City of Semarang, forms of adolescent behavior in the old city area, and shifts in the sociocultural values of the old city after the revitalization. This research method used a qualitative phenomenological design. The results of this study indicate that teenagers who come to the old town have different meanings. Kota Lama is interpreted as a place of horror, tourist attractions, and historical sites. There are five forms of social behavior of adolescents in the old town: traveling, taking photographs, hanging out, studying, and making money. After the revitalization, changes in the old city include physical, violation of values and norms, economy, and culinary places. With an understanding of the sociocultural values of the ancient city, it is hoped that teenagers can behave well in preserving the old city.